2016
DOI: 10.1108/gm-06-2015-0050
|View full text |Cite
|
Sign up to set email alerts
|

How women traverse an upward journey in Indian industry: multiple case studies

Abstract: Purpose -The purpose of this paper is to present multiple case studies of women in leadership roles in India with a view to identifying inhibitors, facilitators and the strategies adopted by them to mitigate the challenges in their odyssey to these positions. The paper contributes to the pivotal subject of under-representation of women in apex positions, which has garnered the attention of researchers in recent years grappling with the identification of the underlying causes. Thus, with a view to narrowing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 71 publications
1
21
0
Order By: Relevance
“…Women have been facing discrimination and unfair treatment at work due to organizational policies and processes (Kanter, 1993). The gendered perceptions (stereotypes and gender roles) at the workplace further create injustice for women (Chawla and Sharma, 2016). The aforementioned causes lead to a feeling of discrimination and stress for working women, which in turn, negatively affects their well-being.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Women have been facing discrimination and unfair treatment at work due to organizational policies and processes (Kanter, 1993). The gendered perceptions (stereotypes and gender roles) at the workplace further create injustice for women (Chawla and Sharma, 2016). The aforementioned causes lead to a feeling of discrimination and stress for working women, which in turn, negatively affects their well-being.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…According to the World Bank Report (2016), women’s participation in the Indian labor force continues to fall from 34.8 to 26.7%, which ought to be a cause for concern for these organizations. Societal beliefs and expectations make working Indian women more vulnerable to stress, as they are expected to not only play dual roles at home and work but also to perform well in the workplace (Naqvi, 2011; Chawla and Sharma, 2016). The Nielsen Survey reports that working Indian women are the most stressed in the world, as 87% of working Indian women reported that they felt stressed, anxious, and unenthusiastic, while 82% said that they had no time to relax.…”
Section: Introductionmentioning
confidence: 99%
“…According to NDTV (2014) Business India report, out of 28% of women entering the workforce, 14.91% reach the middle level and only 9.3% actually make it up to the top level. Extant literature suggests a number of reasons for Indian women’s slow progression in career including the existence of glass ceiling, workplace discrimination, gender stereotyping, family responsibilities and lack of contextual support (Chawla & Sharma, 2016).…”
Section: Career Aspirations Of Women Professionals In the Indian Contextmentioning
confidence: 99%
“…Extant research on women’s career aspirations in the Indian context has emphasized the role of contextual factors such as glass ceiling and discriminatory organizational attitude affecting the career progression of women (Datta & Agarwal, 2017; Chawla & Sharma, 2016; Srinivasan et al, 2013; Dashora, 2013). While some have emphasized the role of internal factors (Menon-Sen & Kumar, 2001; Rajadhyaksha & Bhatnagar, 2000; McKelway, 2018), much of the existing observations are based on qualitative studies.…”
Section: Personal Cognitive Factors Affecting Career Aspirations Of Wmentioning
confidence: 99%
“…There are many studies that discuss either one or more barriers to women entrepreneurship covering different geographic regions around the world. Some of these studies include: multiple barriers (Sharma, 2013;Chawla & Sharma, 2016)), risk-taking by women entrepreneurs, finances (Brindley, 2006;Irwin & Scott, 2010;Sandhu, et al, 2012), career progression (Ismail & Ibrahim, 2008;Chovwen, 2007), ICT (Mathew, 2010), are few studies on similar theme. In the context of Pakistan, there are scholarly studies that do discuss the challenges that women entrepreneurs face.…”
Section: State Of the Artmentioning
confidence: 99%